The magnetic properties of NdMnxCr2−xSi2C (0 < x < 2). (1st December 2015) - Chen, Guofu; Du, Qianheng; Yang, Wenyun; Lai, Youfang; Yang, Jinbo; Wang, Changsheng; Han, Jingzhi; Liu, Shunquan; Zhang, Yan; Du, Honglin; Zhang, Changsheng; Xia, Yuanhua; et al.
Abstract: Carbon was successfully introduced into NdMn x Cr2− x Si2 serial compounds as an interstitial atom. The compounds with x   ⩽  0.5 keep a CeMg2 Si2 -type structure while the structure changes slowly with increasing manganese content. Finally, a new superstructure was found and determined for x around 1.7. All the compounds for x   =  1.1, 1.3, 1.5 and 1.7 have two magnetic phase transition temperatures around 43 and 314 K. What is more, a giant magnetocaloric effect has been observed around the lower phase transition temperature, T R ~ 51 K, in NdMn1.7 Cr0.3 Si2 C. The maximum values of the magnetic entropy change  −Δ S M for the field change of 2 T and 5 T are 14.9 J kg −1 K −1 and 26.0 J kg −1 K −1, which means the interstitial atom effect enhanced the MCE values for 85% and 63% compared to NdMn1.7 Cr0.3 Si2, respectively. NdMn1.7 Cr0.3 Si2 C with first order magnetic transition but low hysteresis losses (thermal  <  ~0.58 K; magnetic field  <  ~0.12 T) can be a candidate for magnetic refrigerator applications in the temperature region near 50 K. Besides, two field-induced magnetic phase transitions were found in NdMn1.7 Cr0.3 Si2 C among the temperature range from 53 to 60 K, and a linear relation between the phase transition field and temperature was found and analyzed.